Validation of the Gait Disorientation Test in children with concussion - Alkathiry, Abdulaziz A.; Alsubaie, Saud F.; Alsalaheen, Bara A.; Whitney, Susan L. (Frontiers in Pediatrics, 2022)
Background Mild traumatic brain injury (mTBI) or concussion is a complex injury that is difficult to diagnose and assess. There are negative impacts on cognition, balance, and mobility after a concussion. The Gait Disorientation Test (GDT) is an objective measure that assesses a person's balance ability by comparing the walking time with eyes open and the walking time with eyes closed in a standardized walking task. The purpose of this study was to assess the validity and the diagnostic properties of the GDT in children with concussions. Methods Thirty-six children with concussions, and 91 controls aged between 9 and 18 years old participated in the study. Participants completed demographics, the GDT, the Functional Gait Assessment (FGA), the Pediatric Vestibular Symptom Questionnaire (PVSQ), and the Pediatric Visually Induced Dizziness Questionnaire (PVID). Results Children with concussions showed higher (worse) GDT scores (M = 2.18 ± 1.93 s) than healthy controls (M = 1.13 ± 0.95 s), which was statistically significant (P = 0.014). Conclusion The GDT was able to distinguish between children with concussions and healthy controls. Given the simplicity of the GDT, it can be used to assist in discriminating between children with and without concussion.